The Customary of the Shrine of St. Thomas Becket at Canterbury Cathedral : Latin Text and Translation. - Jenkins, John. (Foundations Series, 2022)
This facing-page Latin and English edition of the customary for the shrine of St. Thomas Becket at Canterbury Cathedral, provides valuable insights into the management of one of the most popular pilgrimage sites in Europe.